A method of determining effective elastic properties of honeycomb cores based on equal strain energy - Qiu, Cheng; Guan, Zhidong; Jiang, Siyuan; Li, Zengshan (Chinese journal of aeronautics, 2017)
A computational homogenization technique（CHT） based on the finite element method（FEM） is discussed to predict the effective elastic properties of honeycomb structures.The need of periodic boundary conditions（BCs） is revealed through the analysis for in-plane and out-of-plane shear moduli of models with different cell numbers.After applying periodic BCs on the representative volume element（RVE）,comparison between the volume-average stress method and the boundary stress method is performed,and a new method based on the equality of strain energy to obtain all non-zero components of the stiffness tensor is proposed.Results of finite element（FE） analysis show that the volume-average stress and the boundary stress keep a consistency over different cell geometries and forms.The strain energy method obtains values that differ from those of the volume-average method for non-diagonal terms in the stiffness matrix.Analysis has been done on numerical results for thin-wall honeycombs and different geometries of angles between oblique and vertical walls.The inaccuracy of the volume-average method in terms of the strain energy is shown by numerical benchmarks.